HOMOSEKSUAL DALAM PERSPEKTIF AL-QUR’AN - Mustaqim, Abdul (SUHUF, 2016)
One of current and controversial issues in Indonesia is the emergence of LGBT community. They do not only demand that their rights should be respected, but also struggle their marriage between same gender to be legelized by the constitution of marriege. This article aims to explain the ontological view of the Qur’an about sexuality. How does the Qur’an view the issues of sexuality? How to understand contextually the narration of qawm Luth (literraly meaning: ethnic group of Prophet Luth), what are the philosophical values beyond the narration, and how should to behave the community of LGBT properly and humanly? Using contextual-maqâshidî approach the writer aims to elaborate the qur’anic verses relating to the issues of sexuality and the narration of Qawm Luth.